Hacking the Kinect - Kramer, Jeff (Apress, 2012)
Annotation
Online resource; title from PDF title page (EBSCO, viewed November 29, 2017)
Keywords: Video games -- Programming; Multimodal user interfaces (Computer systems); Computer input-output equipment -- Programming; Xbox 360 (Video game console) -- Programming; Jeux vidéo; Programmation; Interfaces utilisateurs multimodales (Systèmes informatiques); Ordinateurs; Équipement d'entrée-sortie; Programmation; Xbox 360 (Console de jeux vidéo); Programmation; COMPUTERS; Programming; Games; Video games; Programming